Uso de dietas de alto grão na terminação de cordeiros em confinamento - Bernardes, Guilherme Meneghello Carvalho (2014)
The experiment was conducted at the Laboratory of Sheep, Federal University of Santa Maria and aimed to evaluate the effect of using different high grain diets on nutrient intake, performance, carcass characteristics, tissue composition of the palette, the feeding behavior and conduct an economic analysis of the supply of lambs finished in feedlot. Thirty-two male castrated Texel breed, born of simple birth and weaned at an average of 50 days old lambs were used. The treatments consisted of different types of grains, not processed, as follows: corn grain, oat grain, oat grain or grain of paddy. The animals were slaughtered when they reached a body weight of pre - established 32kg slaughter, which corresponds to 60 % of mature weight of their mothers. Lambs fed diets with high corn grain have higher intakes of dry matter, organic matter, crude protein, total carbohydrates and total digestible nutrients, and lower intake of neutral detergent fiber. Also present body condition score, weight gain and higher feed conversion, which leads to reduction in the number of days in confinement to reach slaughter weight. Also provide best economic outcome when compared with lambs finished in feedlot diets with the use of top-grain base of oat, oat or rice in the husk. Lambs fed diets with high corn grain have higher weights and yields of hot and cold carcass, better carcass conformation and greater loin eye area when compared to lambs from the other treatments. Also, have a higher state of greasing and back fat thickness at slaughter, which leads to reduction in the rate of break after cooling carcass. The weights of the regional courts were higher in lambs of treatment based on corn grain, although a smaller proportion of leg, most side cut and fat in the palette, a factor that may be undesirable for the consumer market. As for the feeding behavior of feedlot lambs, one can observe that the changes were caused mainly by the voluntary feed intake and the proportion of dietary NDF, but ensuring necessary to maintain rumen health conditions. Thus the use of diets high grain corn, oat, oat or rice in the husk for finishing lambs in feedlot is a viable alternative productive point of view. However, the use of corn grain provides better performance and economic results.